(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The biogenetic antecedents of flavonoids and isoflavonoids, which are abundant in plants, are chalcones. They have antimitotic, antimutagenic, and antitumor-promoting properties, as well as antibacterial, antiviral, anti-inflammatory, and hepatoprotective properties.Claisen condensation of 1:2 moles of 2,4-Diacetyl Resorcinol (DAR) and substituted aldehydes yielded novel bis-chalcones, which were characterized by 1HNMR, and 13C NMR. To determine whether these compounds have antibacterial activity, the disk diffusion method was performed. Microorganisms are Gram-positive and Gram-negative.